- #1

Glissando

- 34

- 0

## Homework Statement

Find the horizontal asymptote of f(x) = (x

^{2}-1)/(x

^{2}-4)

## Homework Equations

Limits

## The Attempt at a Solution

I'm pretty family with the process, I just get confused when there's an x

^{2}in the denominator and no x in the numerator ):

So I already figured out that 1 is the horizontal asymptote, therefore:

lim [f(x) -1]

x->+/- infinity

= lim 3/(x

^{2}-4)

x->+/-infinity

Here's where the problem starts...(just for positive infinity for now), does the above limit become:

lim 3/(infinity

^{2}-4)

x->+infinity

which I have no idea what it equals to ):

OR

lim 3/+inifinity(0-4) = 0

^{-}

x->+infinity

I hope that makes sense ): Thanks for the help!